Good Corporate Governance and Dividen Policy of Consumer Non Cyclical Sector Companies on Indonesian Stock Market - Muhammad Risal; Henny Setyo Lestari (Peneliti.net, 2022)
This study aims to analyze the effect of good corporate governance (GCG) on dividend policy with the independent variables board size, board independent, institutional ownership on the dependent variable, namely dividend payout ratio (POUT) and dividend yield (YD). The data used in this study is secondary data sourced from the annual reports of non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (IDX) during the 2017-2021 period. The research sample was selected using purposive sampling method in order to obtain 30 companies as samples. The data analysis used to test the hypothesis is multiple regression analysis using the Eviews 9 program. The results show that the independent board variable has a significant effect on dividend policy. This implies that a higher proportion of board independence cyclical consumer on the Indonesian stock exchange can encourage dividend policy. Meanwhile, the board size and institutional ownership variables have no significant effect on dividend policy.